Predisposing and precipitating risk factors for delirium in gastroenterology and hepatology: Subgroup analysis of 718 patients from a hospital-wide prospective cohort study - Hildenbrand, Florian F.; Murray, Fritz R.; von Känel, Roland; Deibel, Ansgar R.; Schreiner, Philipp; Ernst, Jutta; Zipser, Carl M.; Böettger, Soenke (Frontiers in Medicine, 2022)
Background and Aims: Delirium is the most common acute neuropsychiatric syndrome in hospitalized patients. Higher age and cognitive impairment are known predisposing risk factors in general hospital populations. However, the interrelation with precipitating gastrointestinal (GI) and hepato-pancreato-biliary (HPB) diseases remains to be determined. Patients and methods: Prospective 1-year hospital-wide cohort study in 29'278 adults, subgroup analysis in 718 patients hospitalized with GI/HPB disease. Delirium based on routine admission screening and a DSM-5 based construct. Regression analyses used to evaluate clinical characteristics of delirious patients. Results: Delirium was detected in 24.8% (178/718). Age in delirious patients (median 62 years [IQR 21]) was not different to non-delirious (median 60 years [IQR 22]), p=0.45). Dementia was the strongest predisposing factor for delirium (OR 66.16 [6.31-693.83], p<0.001). Functional impairment, and at most, immobility increased odds for delirium (OR 7.78 [3.84-15.77], p<0.001). Patients with delirium had higher in-hospital mortality rates (18%; OR 39.23 [11.85-129.93], p<0.001). From GI and HPB conditions, cirrhosis predisposed to delirium (OR 2.11 [1.11-4.03], p=0.023), while acute renal failure (OR 4.45 [1.61-12.26], p=0.004) and liver disease (OR 2.22 [1.12-4.42], p=0.023) were precipitators. Total costs were higher in patients with delirium (USD 30003 vs. 10977; p<0.001). Conclusion: Delirium in GI- and HPB-disease was not associated with higher age per se, but with cognitive and functional impairment. Delirium needs to be considered in younger adults with acute renal failure and/or liver disease. Clinicians should be aware about individual risk profiles, apply preventive and supportive strategies early, which may improve outcomes and lower costs.